DOES EARLY CHILDHOOD EDUCATION MATTER DURING COVID-19 PANDEMIC: A NARRATIVE REVIEW - Maria Gayatri (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Early childhood is an important milestone in children’s life. The practices of online learning are challenging for families with early childhood children. The study examined the implementation of early childhood education during the pandemic of COVID-19. A narrative literature review of some studies published from the inception of the pandemic COVID-19 to October 31, 2020. The search strategy comprised an electronic search of different online database in PubMed, MEDLINE, Web of Science, Scopus and manual search on Google Scholar by an exploration of a web-based search engine and hand searching. The keywords used in this study were “early childhood”, “education”, online learning”, “pandemic”, COVID-19. Early childhood education has been influenced due to school closure. Most of the children experience online learning, to reduce the spread of the outbreak, especially when face-to-face learning cannot be conducted. Parents and teachers have significant roles in supporting the children to improve their cognitive and social development. However, the implementation of home learning causes some difficulties in relation with self-regulation of very young children, the readiness to utilize of digital technology and learning materials, parent’s beliefs and attitude on online learning compared with traditional learning, and requirements of demanding time and knowledge to accompany the children. Therefore, it is important to have good communication between parents and teachers to support early childhood online learning during the outbreak. Keywords: COVID-19, Early childhood, Education, Online learning, Pandemic.